2021
DOI: 10.1111/jan.15117
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Attachment Through Healing (PATH): Results of a retrospective feasibility study providing trauma‐and‐violence‐informed care to pregnant women

Abstract: Aim To evaluate the impact of a trauma and violence‐informed cognitive behavioural therapy (TVICBT) intervention, compared with standard care on mental health, coping, bonding and maternal‐infant attachment among pregnant women with a history of intimate partner violence and who displayed symptomatology consistent with anxiety, depression or post‐traumatic stress disorder (PTSD). Design A mixed‐methods case study design was employed, where women either received standard perinatal care or were referred to a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Researchers in nursing and health services are actively engaged in developing and evaluating new interventions to address the health effects associated with violence exposure. For pregnant women who have experienced IPV, the provision of 12 sessions of trauma-and violence-informed cognitive behavioural therapy by a clinical nurse specialist is showing promise as an intervention to identify potential triggers in pregnancy, develop appropriate coping strategies and advocate for their needs to best cope with their stressors and pain (Mantler et al, 2023). Similarly, for nurses working with perpetrators of violence, a nurse-led, 15-session videoconference-delivered cognitive behavioural group therapy is also showing promise as an intervention where participants report high levels of satisfaction and completion (Nesset et al, 2023).…”
Section: Org Aniz Ational Supp Ort For Ipv Interventi On Smentioning
confidence: 99%
“…Researchers in nursing and health services are actively engaged in developing and evaluating new interventions to address the health effects associated with violence exposure. For pregnant women who have experienced IPV, the provision of 12 sessions of trauma-and violence-informed cognitive behavioural therapy by a clinical nurse specialist is showing promise as an intervention to identify potential triggers in pregnancy, develop appropriate coping strategies and advocate for their needs to best cope with their stressors and pain (Mantler et al, 2023). Similarly, for nurses working with perpetrators of violence, a nurse-led, 15-session videoconference-delivered cognitive behavioural group therapy is also showing promise as an intervention where participants report high levels of satisfaction and completion (Nesset et al, 2023).…”
Section: Org Aniz Ational Supp Ort For Ipv Interventi On Smentioning
confidence: 99%
“…Authors of the Promoting Attachment through Healing (PATH) study employed a different programmatic approach using cognitive behavioral therapy (CBT) and trauma-and-violence-informed care during the perinatal time [26].…”
Section: Review Of Literaturementioning
confidence: 99%
“…As an example, more women in the TVICBT group indicated that they "prefer no males" before receiving care. During the intrapartum period, researchers reported that 94.6% of TVICBT (35/37) women coped successfully compared to 78.1% (25/32) of women who received standard care [26].…”
Section: Review Of Literaturementioning
confidence: 99%
“…A wide variety of therapeutic approaches have been used to provide support to survivors of perinatal IPV, such as cognitive behavioral therapy (CBT) (Mantler et al, 2022 ), motivational interviewing (Sapkota et al, 2022 ), and problem‐solving therapy (Nakku et al, 2021 ). Counseling sessions are often integrated into pre‐existing prenatal care visits or added as a supplementary program.…”
Section: Introductionmentioning
confidence: 99%